CHARACTERISTICS OF THE EMERGENCE OF PERSONAL CHARACTERISTICS IN CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses gene, reflexes, characteristics, manifestations of qualities, characteristics of traits and characteristics, basic congenital characteristics in a newborn baby. The amount of potential personal traits, people’s quality, the percentage of their correction that is peculiar each person and the effect of psychological and educational correcting work perception among age groups were discussed.